Rapid Degradation Pathways of Host Proteins During HCMV Infection Revealed by Quantitative Proteomics - Lin, Kai-Min; Nightingale, Katie; Soday, Lior; Antrobus, Robin; Weekes, Michael P. (Frontiers in Cellular and Infection Microbiology, 2021)
Human cytomegalovirus is an important pathogen in immunocompromised individuals and neonates, and a paradigm for viral immune evasion. We previously developed a quantitative proteomic approach that identified 133 proteins degraded during the early phase of HCMV infection, including known and novel antiviral factors. The majority were rescued from degradation by MG132, which is known to inhibit lysosomal cathepsins in addition to the proteasome. Global definition of the precise mechanisms of host protein degradation is important both to improve our understanding of viral biology, and to inform novel antiviral therapeutic strategies. We therefore developed and optimised a multiplexed comparative proteomic analysis using the selective proteasome inhibitor bortezomib in addition to MG132, to provide a global mechanistic view of protein degradation. Of proteins rescued from degradation by MG132, 34-47 proteins were also rescued by bortezomib, suggesting both that the predominant mechanism of protein degradation employed by HCMV is via the proteasome, and that alternative pathways for degradation are nevertheless important. Our approach and data will enable improved mechanistic understanding of HCMV and other viruses, and provide a shortlist of candidate restriction factors for further analysis.